James K. Polk Papers : Collection - Library of Congress - Manuscript Division (2021)
"The papers of James K. Polk (1795-1849), governor of Tennessee, representative from Tennessee, Speaker of the House of Representatives, and eleventh president of the United States, contain approximately 20,500 items dating from 1775 to 1891, with the bulk falling in the period 1830-1849. The collection includes correspondence, presidential letterbooks, diaries, speeches and messages, account and memorandum books, family papers, financial and legal records, printed matter, portraits, and other papers relating chiefly to Polk’s political career in Tennessee and on the national level. The papers document struggles during Andrew Jackson’s administration over the Bank of the United States, Nullification Crisis, and internal improvements. For the period of Polk’s presidency, the papers cover the annexation of Texas, war with Mexico, the Oregon question, and the acquisition of the territories of New Mexico and California. Other subjects represented include slavery, tariff issues, patronage and office seeking, plantation matters, and family affairs. The collection also contains three volumes of the papers of Polk's wife, Sarah Childress Polk." [self-dewscription]